Study of plant and soil factors affecting seasonal nitrogen fixation, yield formation and seed composition in soybeans - Moro Rosso, Luiz (Kansas State University, 2021)
Soybean [Glycine max (L.) Merr.] production currently faces several challenges linked to global food security (both quantity and quality) raised by an overgrowing human population, limited cropland, and diversified dietary in developed regions. To sustain seed yield and high protein levels, soybeans depend on large nitrogen (N) uptake, which is mostly attained by the symbiotic N fixation (SNF) process. Although SNF has been extensively investigated with single assessments during the season, just a few recent reports looked at the temporality of N sources (soil and SNF) while taking into consideration seasonal dry matter accumulation and soil nitrate (NO₃) and ammonium (NH₄) availability. Furthermore, it is still unclear how the overall changes in N uptake dynamics supports yield formation and seed components among canopy portions, especially considering the branches as potential contributors for high yield in modern genotypes. Following this rationale, this project presents two overall objectives: 1) to identify the impact of soil NO₃ and NH₄ temporal availability on seasonal SNF [N derived from the atmosphere (Ndfa)], N uptake, and dry matter accumulation (herein called study 1); and 2) to characterize seed yield, protein, oil, amino acids (AA), and fatty acids (FA) from the main stem and branches (herein called study 2) for different commercial soybean varieties. To address the first objective, four genotypes were field grown at Manhattan (Kansas, US) during 2019 and 2020 growing seasons. Dry matter, N concentration, N uptake, Ndfa, fixed N, soil NO₃, and NH₄ (60-cm depth) were measured at six phenological stages, along with seed yield, protein, and oil concentration at harvest time. Seasonal exposure to NH₄ (area under the curve) showed a stronger suppression of Ndfa at the end of the season than NO₃. However, a mid-season NO₃ peak delayed uptake from soil and SNF, but only decreased maximum uptake rates from SNF. Additionally, dry matter was used as a seasonal linear predictor of fixed N to simplify the process model. However, this relationship was deeply affected by soil N availability across environments (boundary functions) and also by a potential dry matter threshold around 5 Mg ha⁻¹ across genotypes and site-years. For the second objective, another four genotypes were field-grown during the 2018 and 2019 growing seasons at Ashland Bottoms and Rossville (Kansas, US), respectively. At harvest time, seeds from the upper, middle, lower main stem, and branch nodes were manually separated and assessed for yield, seed size, protein, and oil (seed content and concentration), abundance of limiting AA within protein, and FA ratio (oleic / linoleic + linolenic). The accumulation of protein was more responsive to node position than oil, determining high protein concentration in the upper main stem and high oil concentration in the lower main stem nodes. However, the protein quality (limiting AA) was higher in the lower main stem, while the FA ratio (oil quality) was greater in the upper section of the plant. Branches presented the less-rich seed composition relative to the main stem, but their contribution to yield was positively associated with oil and limiting AA abundance across genotypes. In summary, the main outcomes of the present thesis are related to 1) the importance of soil NO₃ and NH₄ to regulate Ndfa during the season, 2) the timing of Ndfa assessment or prediction for an accurate fixed N calculation throughout the season, and 3) the underlaying effect of branch yield allocation on the seed composition of the whole soybean plant, plausibly moderating changes across genotypes, environments, and management practices. A better understanding of soybean N acquisition and allocation for yield and quality formation within the plant is important to sustain the yield increase, offset protein decay, and assure cropping systems sustainability and food security in a long-term standpoint.
Keywords: Glycine max; Soil nitrate; Ammonium; Protein; Oil; Seed yield